Comparisons of controlled environment and vineyard experiments in Sauvignon blanc grapes reveal similar UV-B signal transduction pathways for flavonol biosynthesis. (November 2018) - Liu, Linlin; Gregan, Scott M.; Winefield, Christopher; Jordan, Brian
Highlights: first comparison of controlled and vineyard environments to interpret flavonoid biosynthesis in response to high/low UV-B fluence. controlled environments and vineyard trials present similar UV-B responses in flavonol accumulation and gene expression. PR genes were not responsive to the natural UV-B fluence but regulated by berry development. Abstract: UV-B radiation is an environmental challenge affecting a number of metabolic functions in plants. Plants protect themselves from this potentially damaging radiation through synthesising UV-absorbing compounds such as flavonoids. This study aims to investigate the effect of UV-B on flavonoid biosynthesis in Sauvignon blanc grapes. In particular, a comparison has been made between controlled environment (CE) and vineyard trials to better understand molecular mechanisms of low/high fluence UV-B responses and how the results relate to each other in the context of flavonoid biosynthesis. Following exposure to supplemental UV-B in the CE, both flavonols and gene expression exhibited UV-B induced response. Flavonols, particularly quercetin/kaempferol 3- O -glycosides were increased at distinct stages of berry development. All genes measured showed a significant developmental regulation. VvFLS4, VvCHS1, VvMYB12, VvHY5 and PR ( VvTL1 and VvChi4A/4B ) increased due to UV-B in the CE experiments. However, PR were not responsive to the natural UV-B fluence in vineyard but were significantly induced at later stages of development. Overall, despite very different conditions in the CE and vineyard the majority of UV-B induced responses are similar. Only PR activities in the CE cabinets reflect a higher fluence stress response that is not reflected in the natural lower UV-B fluence environment.